1998
DOI: 10.1161/01.res.83.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine Enhances Cytokine-Induced Interferon Gamma Expression in Human T Lymphocytes

Abstract: Accumulation of substantial numbers of activated T lymphocytes, as well as monocyte/macrophages, in focal areas of arterial intima appears to be a hallmark of atherogenesis. Our previous report demonstrated that lysophosphatidylcholine (lyso-PC), a polar phospholipid component that is increased in atherogenic lipoproteins and atherosclerotic lesions, can upregulate the expression of heparin-binding epidermal growth factor-like growth factor and the interleukin (IL)-2 receptor in cultured human peripheral T lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…The proinflammatory function of LPC, produced by PLA 2 , is described mainly in relation to atherosclerosis involving endothelial cells, smooth muscle cells, macrophages, and T-cells (Cieslik et al, 1998;Kume and Gimbrone, 1994;Kume et al, 1992;Morimoto et al, 2001;Nishi et al, 1998;Ochi et al, 1995;Oka et al, 2000;Sakata-Kaneko et al, 1998). LPC are also implicated in neurodegenerative disorders which exhibit considerable extents of neuroinflammation including Parkinson's disease, multiple sclerosis, and cerebral ischemia (Andreoli et al, 1973;Kinouchi et al, 1990;Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proinflammatory function of LPC, produced by PLA 2 , is described mainly in relation to atherosclerosis involving endothelial cells, smooth muscle cells, macrophages, and T-cells (Cieslik et al, 1998;Kume and Gimbrone, 1994;Kume et al, 1992;Morimoto et al, 2001;Nishi et al, 1998;Ochi et al, 1995;Oka et al, 2000;Sakata-Kaneko et al, 1998). LPC are also implicated in neurodegenerative disorders which exhibit considerable extents of neuroinflammation including Parkinson's disease, multiple sclerosis, and cerebral ischemia (Andreoli et al, 1973;Kinouchi et al, 1990;Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that LPC has immunomodulatory functions as it induces the expression of multiple genes relevant to inflammation including cytokines and chemokines, adhesion molecules, growth factors and proinflammatory enzymes in endothelial cells, smooth muscle cells, macrophages, and T-cells (Cieslik et al, 1998;Kume and Gimbrone, 1994;Kume et al, 1992;Morimoto et al, 2001;Nishi et al, 1998;Ochi et al, 1995;Oka et al, 2000;Sakata-Kaneko et al, 1998). LPC is also reported to inhibit expression of some genes in inflammatory responses including interferon g (IFNg)-induced Th1-cell-specific chemokines such as IFNg-inducible protein (10 kDa), monokine induced by IFNg and IFN-induced T-cella chemoattractant (Sheikh et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These recruited macrophages further upregulate the inflammatory disease and participate in the progressive demyelinating disease process in Krabbe disease and in twitcher mice. LPC is known to act as a chemoattractant for monocytes (55) and T lymphocytes (56,57) and also enhances the production of interferon-g by activated T cells, thus promoting an inflammatory reaction (58,59). Because elevated levels of LPC are observed in Krabbe and twitcher brain, it can be postulated that LPC may, at least in part, be responsible for the inflammatory response observed in Krabbe disease and in twitcher mice.…”
Section: Discussionmentioning
confidence: 99%
“…LPC has many effects that are expected to play important roles in atherogenesis. 18) For example, LPC stimulates cytokine, 19) adhesion molecules, 20) growth factor population, 21) and apoptosis induction. 22) Many studies have identified that cell apoptosis increased in atherosclerotic plaques compared with normal vascular vessels.…”
Section: Discussionmentioning
confidence: 99%